HUBUNGAN BEBAN OTOT TANGAN AKTIVITAS PENGETIKAN NASKAH BALI DENGAN KEYBOARD QWERTY TERHADAP HASIL BELAJAR - Suhartana, I KG; ., N Adiputra; ., K Tirtayasa; Sutjana, I Dewa Putu (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 2 No 2 (2016): Volume 2 No 2 Desember 2016, 2016)
As a human tools, computer is used in various sectors of human life, for examples: writing documents, playing  multimedia  and so on.  Making document withBalinese charactersusing a computer has many obstacles such as letters, points, and sign in Balinese charactershave different forms with letters, points, and sign in alphabetic. Another difficulty is the keyboard that is commonly used is not specific to type Balinese script. This research was aimed to determine the correlation between a decrease of  hand muscles load activity typing Balinese scripts with QWERTY keyboard on the increase in learning outcomes. This research was done by using descriptive correlation. Samplesof this research were 23 students who meet the inclusion and exclusion criteria were selectedrandomly. The correlation test results showed that there is a strong correlation between a decrease hand muscle load with the learning outcomes of r xy = -0.963 and p = 0.001. This shows that there is a significant correlation between a decrease hand muscle load with increase learning outcomes with p <0.05. There is a strong correlation and significant between a decrease hand muscle load with increase learning outcomes on Balinese typing activity usingQWERTYkeyboard
Keywords: Balinese Script; Hand Muscle Load; Learning Outcome